The use of manga for the teaching of reading: An investigation on the insertion of japanese literature with elementary school students - Lima, Elielma de Oliveira (Seven Editora, 2023)
Mangas can be seen as a teaching tool, enabling the student to be the protagonist of the process of encounter between the word and the subject who reads and establishing an experience that can modify the conception that both have of the world and their own existences. The main objective of this article is to investigate the acceptance of the use of Manga as a methodological practice in the classroom, as well as to analyze the contribution that it has been bringing to students after a school period by participating in activities with readings with this new literature. In order to verify the students’ acceptance of this methodology, we conducted an investigation study of the initial conceptions through an investigative questionnaire. With the result of the investigation, it was possible to find elements that enable the use of manga as part of the teaching and learning process and also realize the potential of such materials as didactic resources capable of contributing to the mediation in the teaching of contents and concepts of Portuguese Language and New Literatures. DOI:https://doi.org/10.56238/ptoketheeducati-046